An investigation on the use of Venturi weirs as an aerator - Baylar, A (Canadian Assoc Water Quality, 2003)
The most classic example of a hydraulic structure where gas transfer occurs is a weir. Transfer of gases between the atmosphere and river water can occur in a free overfall jet from a weir. A free overfall jet from a weir plunging into downstream water causes entrainment of air bubbles if the free overfall jet velocity exceeds the critical value where aeration occurs. This paper investigates the free overfall jets from Venturi and rectangular notch weirs and their effect on air entrainment rate. A Venturi weir was placed at the upstream channel end in order to increase the flow velocity of the free overfall jet and, in turn, to increase air entrainment. It was demonstrated that the air entrainment rate of the Venturi weir is significantly better than the rectangular notch weir, and this advantage becomes more pronounced as the throat width of the Venturi weir is decreased. These results demonstrated that Venturi weirs can be used as highly effective aerators in streams, rivers, constructed channels, fish hatcheries, water treatment plants, etc. Moreover, a regression equation was obtained for the Venturi weirs, relating air entrainment rate to unit discharge, weir crest width, drop height and throat width of Venturi weir. There was good agreement between the measured air entrainment rates and the values computed from the predictive equation.
Keywords: air entrainment rate; aeration; jet expansion; Venturi; weir